2014
DOI: 10.17576/pengurusan-2014-42-05
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Directorships and the Monitoring Role of the Board of Directors: Evidence from Malaysia

Abstract: This study aims to examine the relationship between multiple directorships and the monitoring role of the board of directors in Malaysian listed companies (PLC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…The finding indicates that as the multiple directorships held by each director change, no benefits arise and no costs are imposed on a company's profitability. The current results therefore contradict the findings reported by Kamardin et al (2014) that showed directors serving on multiple boards could have numerable commitments; as a result of which, they are not able to fulfill all of their responsibilities. These results contradict the agency theory and busyness hypothesis that high multiple directorships decrease the financial performance of a firm.…”
Section: Regression Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…The finding indicates that as the multiple directorships held by each director change, no benefits arise and no costs are imposed on a company's profitability. The current results therefore contradict the findings reported by Kamardin et al (2014) that showed directors serving on multiple boards could have numerable commitments; as a result of which, they are not able to fulfill all of their responsibilities. These results contradict the agency theory and busyness hypothesis that high multiple directorships decrease the financial performance of a firm.…”
Section: Regression Analysiscontrasting
confidence: 99%
“…Researchers have provided several definitions for the concept of multiple directorships; for instance, it is defined as the number of external appointments held by directors (Kamardin et al, 2014), or directors who serve on two or more boards (Chou et al, 2014).…”
Section: Literature Review and Hypothesis Development 21 Multiple Directorshipsmentioning
confidence: 99%
See 3 more Smart Citations